Models and Practices of Corporate Governance Worldwide - Mihaela Ungureanu (CES Working Papers, 2012)
In the current context of globalization, we can no longer talk about increasing organizational value ignoring the interests of shareholders, employees, business partners, etc. Such interests may come into conflict, leading to internal conflicts, with negative influence on the entity's performance. To avoid such discrepancies, a responsible behavior from managers is increasingly necessary, which means, in fact, adopting a corporate governance model. The aim of this article is to make a comparative study between the main corporate governance models used globally by analyzing strengths and weaknesses for each one, in the sense to determine which one is the best model and if it can be adapted to different economic systems, in order to be applied on a scale as large. We used a bibliographic method for our research is the one. Literature does not provide concrete answers to this problem, most authors treating each one the governance model specific to their home country.
Keywords: G34; O16; M14; M41; 330; corporate governance; model; control; market; efficiency Romania